2013
DOI: 10.1111/pai.12107
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict severe reactions during peanut challenges in children?

Abstract: Although predictors of positive FCO could be identified, none of the studied risk factors could predict a severe reaction during peanut challenge. When challenging a child sensitized to peanut, clinicians should be prepared and equipped to handle any reaction in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
5
26
0
2
Order By: Relevance
“…Also patient 2 presented with serious gastrointestinal problems having in addition to a high titer of sIgE against Ara h 2 coeliac disease as a co-morbidity. Although a number of four patients does not allow us to draw conclusions concerning the predictive value of Ara h 2 these observations underline the findings of van Erp et al [7] who have shown that Ara h 2 is predictive for a positive outcome in a food challenge, but its relation to severe reactions is insignificant [8]. One year after reaching maintenance patient four had accidently taken a considerable higher amount of peanut protein resulting in an itchy throat.…”
Section: Discussionsupporting
confidence: 40%
“…Also patient 2 presented with serious gastrointestinal problems having in addition to a high titer of sIgE against Ara h 2 coeliac disease as a co-morbidity. Although a number of four patients does not allow us to draw conclusions concerning the predictive value of Ara h 2 these observations underline the findings of van Erp et al [7] who have shown that Ara h 2 is predictive for a positive outcome in a food challenge, but its relation to severe reactions is insignificant [8]. One year after reaching maintenance patient four had accidently taken a considerable higher amount of peanut protein resulting in an itchy throat.…”
Section: Discussionsupporting
confidence: 40%
“…Severity appears to relate to the amount of nut ingested [44]. Hospital-based challenges are not helpful in predicting severity of accidental reactions [45][46][47].…”
Section: Risk Factors For Severe Reactionsmentioning
confidence: 97%
“…Furthermore, challenges are usually terminated at the onset of objective and generally mild symptoms, so the relationship between dose and severity is poorly described. The available data (from studies that have included those with previous anaphylaxis) suggest that peanut-allergic individuals with a history of anaphylaxis are not more sensitive to low doses than those without (29,(41)(42)(43). In a unique study, Wainstein et al performed food challenges in 27 peanut-allergic children; in contrast to other studies, challenges were not stopped following the onset of mild symptoms, but allowed to progress (44).…”
Section: Dose Of Allergenmentioning
confidence: 99%